Endothelial dysfunction as a major cardiovascular risk factor limiting the performance of young athletes: assessment and correction with specialized food products based on apian and herbal components - V. N. Kim; G. A. Prosekin; Yu. N. Fedosov; S. O. Klyuchnikov; S. A. Parastaev (National Electronic Information Consortium (NEICON), 2020)
Objective: to assess with exercise tests the endothelial dysfunction (ED) and performance before and after the treatment with specialized athlete's nutrition product (SANP) with apian and herbal components. Materials and methods: 88 athletes aged 16-18 we tested. The main group included 58 athletes, who took SANP (candy bar «Gold F25 ApiSpeis Light») for 2 months. The control group-1 included 32 schoolchildren and students, non-athletes, with normal endothelium-dependent vasodilatation function of the brachial artery (EDVD BA) at the peak of the reactive hyperemia test (RHT). Control group-2, 30 athletes who did not take SANP, was formed for the comparison with the main group after taking SANP. For all individuals, we evaluated the level of EDVD, endothelium-dependent vasoconstriction (EDVC BA) at the peak of the hyperventilation test (HVT), the coefficients (C) of the endothelial sensitivity to shear stress and the blood flow velocity (Vps) of the BA at the peak of the RHT and HVT, the endothelial sensitivity index (ESI), and the maximum load (Wmax), the anaerobic threshold time (ATT). We also did general and biochemical blood tests. Results: the earliest manifestation of endothelial dysfunction is a decrease in sensitivity to shear stress during RHT and HVT resulting from endotheliocyte overstrain which can be assessed with ESI (sensitivity 80.9%, specificity 99.4 The EDVD diagnostic significance was 5.6 times lower than that of EIS, while 10.5% of athletes with over 10% EDVD actually had ED, with a predominant vasospasm and high cardiovascular risk. After the course of SANP in the main group, EDVD increased by 70%, EDVC decreased by 2.2 times, and the ESI increased by 2.3 times, against the background of improved performance. Total cholesterol decreased by 13%, triglycerides by 17%, cortisol by 14%, lactate by 25%. Red blood cell and mineral levels increased. A correlation was found between an increase in ATT a decrease in cortisol (r=-0.53; p<0.0001), an increase in red blood cells (r=0.62; p<0.0001), and an increase in Vps in BA during of hyperventilation with an increase in Wmax (r=0.52; p<0.0001). Conclusions: ED is the main factor of cardiovascular risk, limiting working capacity and forming a spastic type of regional hemodynamics of young athletes. The ESI criterion enables the detection of a decrease in the endothelial sensitivity to shear stress during a hyperventilation test, which causes the predominant vasospasm. Th e tested SANP can be used in the system of biomedical support for young athletes.